ANALISIS FINANSIAL USAHATANI PADA BERBAGAI TINGKAT KECEPATAN ADOPSI VARIETAS UNGGUL KEDELAI - Hutapea, Yanter (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2011)
To increase the productivity of soybean, the use of high yielding varieties is one of the main things that must be considered. The speed of farmers in adopting varieties is different among the farmers, which will lead the differences in farm management. This study aims to determine the efficiency of farming on different levels of adoption speed. This activity was conducted in March through December of 2009. Implementation of survey by interviewing the farmer, conducted in Gunung Kembang Village, Merapi District, Lahat Regencies; Sukomulyo Village, Tugumulyo District, Musi Rawas Regencies and Margomulyo Village, Bayung Lencir District, Musi Banyuasin Regencies. Sample was taken by Disproportionate Stratified Random Sampling Method. The sample consists of three strata of farmers who adopt released varieties 1-2 planting season since recommended, 3-4 and 5-6 planting season since recommended, with a total sample of 114 farmers. The results showed that soybean production is produced by farmers who adopt released varieties 1-2 planting season since recommended, 3-4 and 5-6 planting season sincerecommended is 1443.36 kg/ha; 1423.07 kg/ha and 1133.75 kg/ha with net income is Rp 3.742.255/ha; Rp 3.554.105/ha and Rp 2.240.925/ha. The level of efficiency (R/C) reached 1.58, 1.53 and 1.39 respectively.